PETA SEBARAN SALINITAS PADA SUMUR BOR DI KELURAHAN BELAWAN II KECAMATAN MEDAN BELAWAN - Intan Iksaura Ginting; Yunus Afifuddin; Desrita Desrita (AQUACOASTMARINE, 2014)
People activity in sub district Medan Belawan II require very large. The purpose of this research was to analyze of salinity values and the type of water well drilling in the area of research, analyze the effect of depth of the well to salinity value, analyze salinity distribution map and figuring out how to manage water resources in Belawan II village. This research was conducted on june-july 2013 in village Belawan II, Subdistrict Medan Belawan, Medan. This research used ArcGIS 10 to got a map of the distribution of salinity. The result showed that number of wellbore included in good classification (333mg/l) was 4%, permitted (666-1333 mg/l) was 27%, doubting (1666-2000 mg/l) was 46% and dangerous (2333-3000 mg/l) was 24%. Freshwater was 4%, between fresh water and brackish water was 27% and brackish water was 69%. at a depth of 65-100m, were included in dangerous category was 24%, suspect 18%, allowed 1% and good category not found. At a depth > 100 meters the waters were included in the hazardous category not found, suspect 9%, allowed 44%, and good category was 4%. The most dominating salinity distribution was 1666 mg/l-2000 mg/l were included in suspect category. The most dominating salinity distribution was 1666 mg/l-2000 mg/l were included in suspect category. This result showed that intrusion has occurred in the wellbore, and the water quality wasn’t good to serve as drinking water.Keyword : Intrusion, Salinity, Wellbore